Identifying at risk populations amongst breast cancer survivors and their common symptoms and concerns - Pooja Roy; Iuliia Kovalenko; Janet Chan Gomez; Kit Lu; Beth Rudge; Yijin Wert; Lisa Torp (BMC, 2023)
Abstract Purpose The survival rate amongst breast cancer survivors (BCS) have been increasing, with a 5-year survival rate of almost 90%. These women face many quality of life (QOL) issues either due to either cancer itself or the complex treatment regimen. Our retrospective analysis aims to identify at risk populations among the BCS and their most common concerns. Methods This is a single-institution, retrospective, descriptive analysis of patients who were seen at our Breast Cancer Survivorship Program from October 2016 to May 2021. Patients completed a comprehensive survey which assessed self-reported symptoms, their concerns and degree of worry and recovery to baseline. The descriptive analysis on the patient characteristics included age, cancer stage and treatment type. The bivariate analysis included the relationship between the patient characteristics and their outcomes. Analysis of group differences was completed with Chi-square test. When the expected frequencies were five or less, Fisher exact test was used. Logistic regression models were developed to identify significant predictors for outcomes. Results 902 patients (age 26-94; median 64) were evaluated. Majority of women had stage 1 breast cancer. The most common self-reported concerns affecting the patients were fatigue (34%), insomnia (33%), hot flashes (26%), night sweats (23%), pain (22%), trouble concentrating (19%), and neuropathy (21%). Though 13% of BCS felt isolated at least 50% of their time, the majority of patients (91%) reported having a positive outlook and felt that they have a sense of purpose (89%). Younger patients were more likely to worry about their cancer more than 50% of the time (p < 0.0001). Patients that were less likely to return back to at least 50% of their pre-treatment baseline were younger (age ≤ 45) (p = 0.0280), had higher stage breast cancer (Stage 2-4) (p = 0.0061), and had chemotherapy either alone or as part of their multi-modality treatment (p < 0.0001). Conclusion According to our study, younger patients, those with higher stage breast cancer and survivors who had chemotherapy may experience significant QOL issues. Fortunately, majority of BCS report a positive and optimistic outlook post treatment. Identifying common concerns after treatments and vulnerable populations are especially important to deliver quality care and to optimize interventions. Implications for Cancer Survivors Our study identified the most common self-reported concerns affecting BCS. In addition, our results suggest that younger patients, patients with higher stage breast cancer and survivors who had chemotherapy were more likely to have QOL issues. Despite this, our study showed, the majority of BCS reported positive outlooks and emotions.